(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2019)
A comprehensive approach like combining the natural medicine and CUS model for evaluating it as anti-depressant would be productive. Fenchone screened for anti-depressant activity in CUMS model using Fluoxetine as standard. Wistar albino rats were selected to CUMS procedure for 28 days and all the period test substance was administered at doses of 400 mg/kg and 800 mg/kg and at the end of the treatment behavioural and biochemical parameters were analyzed and histopathology findings were observed. CUMS exposure caused a depression like behavior corroborated by the increased immobility time in Despair swim test. In Actophotometer decreased locomotor activity and in the hole board test a decrease in the number of head dips and line crossings. Biochemical findings revealed that decreased serum oxide dismutase and catalase. Fenchone at the doses tested produced significant effects on behavioral and biochemical tests when compare to CUS group. These results manifested that Fenchone had specifically anti-depressant like effect in vivo. In conclusion, the present study advocate that the repeated administration of Fenchone notably reversed CUMS induced depression and oxidative damage and possessed antidepressant like effects, which would be of therapeutic interest for using Fenchone in the treatment of depressive disorders.